Phosphine resistance in North American Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae) - Cato, Aaron (Kansas State University, 2015)
Resistance of stored-grain insects to the fumigant gas phosphine is becoming common, due to genetic-based resistance. Using proper resistance management, phosphine can continue to be effective with efficient monitoring methods. This thesis focuses on assessing the levels of phosphine resistance across North America in a common stored-product pest, the red flour beetle, Tribolium castaneum (Herbst), and on refining a rapid bioassay method so that resistance can be easily and accurately detected. Previous work found that phosphine resistance was present in two regions of the USA, the Southeast and Midwest. In this study a discriminating-dose bioassay was used with adult beetles to determine the number of resistant and susceptible individuals in a test population. Adult T. castaneum from 25 locations across the United States and Canada were collected, and 25-60 adults from each population were assessed for the percentage of resistant individuals. Thirteen populations were deemed susceptible with no resistant insects in the samples, while eight populations had 52% or fewer individuals scored as resistant, and four populations had between 88 and 100% resistant individuals. Dose-mortality experiments were conducted to characterize the “strength” of resistance. One population with 41% resistant beetles in the discriminating dose assay was 4.5-fold resistant relative to the susceptible laboratory strain, compared to 127-fold resistant for a population with all 100% scored as resistant. Adult beetles from twelve populations were used to determine if a “knockdown” test of insects exposed to a high concentration of phosphine (3000 ppm) could assess resistance as well as the discriminating-dose mortality assay. The time required for five out of ten beetles to be knocked down, called the KT[subscript]50 for the time to knockdown 50% of the sample, was useful to characterize resistance. Phosphine susceptible beetles had KT[subscript]50 values less than 15 minutes, while samples from resistant populations had KT[subscript]50’s between 15 and 52 minutes. The refined quick test and knowledge of current levels of phosphine resistance in the United States and Canada reported in this thesis point to the importance of such information in developing phosphine resistance management programs for grain insects.
Keywords: fumigation; stored grain; pest management; insecticide resistance; beetle; insect; Entomology (0353)